From the Ruins of Empire: Ecclesiastical Networks and Spanish Presence in Africa, 1898–1938 - Rodríguez Lago, José Ramón (Journal of religion in Africa, 2022)
After Spain lost its overseas territories, Spanish priests increased their presence in Africa. From an analysis of the bibliography and the press of the time as well as of the different documents issued by the nunciature of Madrid, the Sacred Congregation for the Propagation of the Faith and the Secretariat of State of the Vatican, it is possible to draw some significant conclusions about the evolution of Spanish missions in the Protectorate of Morocco and Spanish Guinea in the four decades which separate the so-called Disaster and the propagandistic myth of the Crusade represented by Francoists – and Africanists – during the Civil War.